Configuration optimization of solar-driven low temperature district heating and cooling system integrated with distributed water-lithium bromide absorption heat pumps. (15th March 2023) - Sun, Fangtian; Xu, Wanqing; Chen, Hongbing; Hao, Baoru; zhao, Xiaoqing
Highlights: SACOP of the LDHC-SAHP is about 0.73 smaller than that of the LDHC-HAHP. Energy transfer process of LDHC-HAHP is more advanced than that of LDHC-SAHP. Centralized and distributed thermal storages can solve solar energy time-discrepancy. Half-effect absorption heat pump is more suitable for the new proposed scheme. SACOP and economic heat transmission distance of LDHC-HAHP are about 11.6 and 18 km. Abstract: Developing solar energy source for space heating and cooling contributes to achieving the target of China's carbon emission peak by 2030. However, the conventional solar-driven heating systems integrated with heat pump or natural gas boiler are featured by short economic heat transmission distance and small solar fraction, and can't cover the demand of the large-scale solar-driven district heating and cooling systems. To solve the problem, two configurations of solar-driven low temperature district heating and cooling system are proposed. One is integrated with distributed single-effect water-lithium bromide absorption heat pumps, and the other is integrated with distributed half-effect water-lithium bromide absorption heat pumps. The distributed absorption heat pumps are located in the energy stations for reducing return temperature of the primary network, which helps to enlarge temperature difference between supply and return and improve solar collector performance. The analyzed results indicate that, in the energy station, replacing single-effect water-lithium bromide absorption heat pump by half-effect one can improve system annual coefficient of performance by about 0.73, reduce cooling cost by about 6.04 ¥/GJ, and increase economic heat transmission distance by about 2.6 km. Thus, the proposed solar-driven low temperature district heating and cooling system integrated with distributed half-effect water-lithium bromide absorption heat pumps has an advanced energy conversion and transfer process, and its economic heat transmission distance is about 18.3 km. Thus, application of the proposed solar-driven low temperature district heating and cooling system integrated with distributed half-effect water-lithium bromide absorption heat pumps would be promising in Northern China.